Prenatal assistance of a secondary care service - doi:10.5020/18061230.2006.p216 - Emanuelle Teixeira da Silva; Joselany Afio Caetano; Ângela Regina de Vasconcelos Silva (Universidade de Fortaleza, 2012)
This exploratory descriptive study, developed at Integrative Medical Assistance Center (NAMI) in Fortaleza-CE, had as objectives to know about the prenatal care offered to pregnant women, based on the criteria established by the Health Ministry's Prenatal and Birth Humanization Program; to trace the social-demographic profile of pregnant women submitted to prenatal care follow-up and to investigate the knowledge of pregnant women regarding the examinations performed during pregnancy. Data were collected by means of interviews with thirty pregnant women above 18 years old, at the end of their pregnancies, in the period of September to October, 2004. Of these, 63% (19) had previous pregnancies, and 67% (20) of the predominant age group were between 19 and 25 years old. As for marital status, 73% (22) reported being married or having a stable relationship. 60% (18) reported having a family income between 1 and 3 minimal wages. Also, 40% (12) claimed to work as housemaids. When questioned about pre natal care, 80% (24) of the women acknowledged that it was essential for the pregnancy to run its course without incidents, and 83% (25) were familiar with the examinations carried out during the prenatal period. The percentage of pregnant women that had performed routine examinations was 77% (23). According to the statements on the medical assistance provided by NAMI, an average of 93% (28) of the women began the prenatal care in the first 14 weeks, attending six or more medical appointments and completing the anti-tetanus immunization schedule. In conclusion, 93% (28) of the interviewed women knew that they would benefit from the medical appointments and knew which procedures were performed during prenatal care.